Menanamkan Karakter Pancasila Dan Wawasan Kebangsaan Pada Generasi Milenial Di SMK Pustek Serpong Tangerang Selatan - Pujilestari, Yulita; Sari, Dewi Purnama; Marlina, Lina (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2024)
People's behavior in life is too focused on technological developments. This is an attitude that deviates from the Pancasila character, where today's children lack a sense of caring for each other, lack respect for others, think about themselves, and are selfish. Problems related to character or morals today are much more common than those that occurred in the past. The issue of character decline, especially in the younger generation, is a matter of collective thought because the young generation is an asset for a country that will play a role in the future. National insight is a perspective on the characteristics that mark a national group. National insight is a conception of perspective based on self-awareness as a citizen of a country regarding oneself and one's environment in the life of the nation and state. National insight is a deep understanding of the identity, history, culture, and values inherent in a nation. This involves awareness of unity, diversity, and responsibility for the development of the country. The concept of Indonesian nationality aims to build and develop unity and integrity. The first goal of national insight is to create a nation that is strong, harmoniously united, highly competitive, and prosperous. These include Pancasila, the 1945 Constitution, the Unitary State of the Republic of Indonesia (NKRI), and Bhinneka Tunggal Ika. On that occasion, he explained the implementation of Pancasila in social life.